PERILAKU PENGUNJUNG WISATA PANTAI WAKA DI DESA FATKAUYON KECAMATAN SULABESI TIMUR KABUPATEN KEPULAUAN SULA PROVINSI MALUKU UTARA - Buamonabot, Gussafril; Rumampuk, Selvie; Mawara, Jetty E. T. (HOLISTIK, Journal Of Social and Culture, 2021)
The development of the tourism sector in North Maluku continues to be carried out in line with increasingly open transportation access. This is in the background by its enchanting natural conditions and natural coupled with a wealth of cultures and customs that are very diverse. Waka Beach located at the end of Sulabesi Island with the beauty of white sand that stretches wide along the beach makes it have its own uniqueness that makes tourists want to linger while on Waka Beach. The natural atmosphere that is still awake is characterized by trees that are still shady adding to the coastal beauty of Waka Beach, the underwater nature also offers its own beauty for every visitor who wants to dive there are interesting diving and snorkeling spots to explore.Factors that influence visitors to visit this Waka Beach tour is, the first is the internal factor or driving factor that comes in visitors themselves, visitors who come because they want to relax after finishing busy with work. Then there are also external factors the emergence of this factor due to curiosity about the beauty of Waka Beach tourism seen on social media as well as those who hear stories from friends who have visited then the emergence of curiosity to visit.Keywords: visitors, tours, behavior